Investigation of Teachers Anger Control Problems - Mertoğlu, Münevver (My University, 2018)
The aim of this research is to determine the reasons for the anger levels of teachers and administrators considering some variables and to recommend sustainable changes to the school system. To analyse the data the Kruskal−Wallis test and other statistical measures were used. The results show that while there is no significant relationship with gender, other seniority and socio-economic status of teachers in the sixth, seventh, and eighth grade have meaningfully higher anger test points than primary and high school teachers. The external anger points are significantly lower among the teachers who like their professions versus those who do not like their profession. As a result, sustainable anger management programmes in schools via seminars or training sessions can contribute to changing teachers’ attitudes towards their students by providing information about the nature of adolescence, and solutions to addressing the challenges of working with them.
Keywords: sustainable education; anger management program; adolescence